PENGARUH STRES KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TERHADAP KINERJA KARYAWAN PT ASKRINDO (PERSERO) CABANG SEMARANG - Bella Octavian Dini; Handoyo Djoko Waloejo (Jurnal Ilmu Administrasi Bisnis, 2018)
The purpose of this study is to determine the effect of work stress and Organizational Citizenship Behavior (OCB) to the employee’s performance of PT Askrindo (Persero) Branch Semarang. This type of research is explanatory research. Sampling technique using sensus sampling technique. The number of samples taken as many as 33 respondents, which are the employee of PT Askrindo (Persero) Branch Semarang. In this study assisted by IBM SPSS 21.0 system. The results showed that work stress influence the employee’s performance by contributing 77.7% while the rest is influenced by factors other than work stress. Organizational Citizenship Behavior (OCB) influences the employee’s performance by contributing 44.9% while the rest is influenced by factors other than Organizational Citizenship Behavior (OCB). Meanwhile, simultaneously and work stress and Organizational Citizenship Behavior (OCB) influence to employee’s performance by donating 78.5% while the rest influenced by factors other than work stress and Organizational Citizenship Behavior (OCB). Based on the calculation of Test F shows that there is a significant influence between work stress and Organizational Citizenship Behavior (OCB) to employee’s performance. This means the lower the work stress and the higher the Organizational Citizenship Behavior (OCB), the higher the employe’s performance of PT Askrindo (Persero) Branch Semarang. In addition, the Organizational Citizenship Behavior (OCB) has the most dominant influence with regression keofisien value of 0.125. Suggestions in this research is to decrease the work stress of employees improve the Organizational Citizenship Behavior (OCB) of employee and the awareness, so it can improve the employee’s performance.